Answer:
1232i34iu494232759375r
Step-by-step explanation:
Answer:
The correct option is 2 .
Therefore ,the missing denominator of the solution. 4 plus or minus the square root of 2, all over is <u> 2 . </u>
![x=\dfrac{4\pm\sqrt{2}}{2}](https://tex.z-dn.net/?f=x%3D%5Cdfrac%7B4%5Cpm%5Csqrt%7B2%7D%7D%7B2%7D)
Step-by-step explanation:
For a Quadratic Equation ax² + bx + c = 0
By Formula Method we get
![x=\dfrac{-b\pm\sqrt{b^{2}-4ac}}{2a}](https://tex.z-dn.net/?f=x%3D%5Cdfrac%7B-b%5Cpm%5Csqrt%7Bb%5E%7B2%7D-4ac%7D%7D%7B2a%7D)
So we have Quadratic Equation is 2x² - 8x + 7 = 0
On Comparing we get
![a=2\\b=-8\\c=7](https://tex.z-dn.net/?f=a%3D2%5C%5Cb%3D-8%5C%5Cc%3D7)
Substituting a , b, c values we get
![x=\dfrac{-(-8)\pm\sqrt{(-8)^{2}-4(2)(7)}}{2(2)}\\\\x=\dfrac{8\pm\sqrt{64-56}}{4}\\\\x=\dfrac{8\pm\sqrt{8}}{4}\\\\x=\dfrac{8\pm2\sqrt{2}}{4}\\\\x=2(\dfrac{4\pm\sqrt{2}}{4})\\\\x=\dfrac{4\pm\sqrt{2}}{2}](https://tex.z-dn.net/?f=x%3D%5Cdfrac%7B-%28-8%29%5Cpm%5Csqrt%7B%28-8%29%5E%7B2%7D-4%282%29%287%29%7D%7D%7B2%282%29%7D%5C%5C%5C%5Cx%3D%5Cdfrac%7B8%5Cpm%5Csqrt%7B64-56%7D%7D%7B4%7D%5C%5C%5C%5Cx%3D%5Cdfrac%7B8%5Cpm%5Csqrt%7B8%7D%7D%7B4%7D%5C%5C%5C%5Cx%3D%5Cdfrac%7B8%5Cpm2%5Csqrt%7B2%7D%7D%7B4%7D%5C%5C%5C%5Cx%3D2%28%5Cdfrac%7B4%5Cpm%5Csqrt%7B2%7D%7D%7B4%7D%29%5C%5C%5C%5Cx%3D%5Cdfrac%7B4%5Cpm%5Csqrt%7B2%7D%7D%7B2%7D)
Therefore ,the missing denominator of the solution. 4 plus or minus the square root of 2, all over is <u> 2 . </u>
Answer:
we conclude that in the second step, 3 should have been subtracted from the right side as well on the left side.
Step-by-step explanation:
Given the expression
![4 < -2x + 3 < 9](https://tex.z-dn.net/?f=4%20%3C%20-2x%20%2B%203%20%3C%209)
SECOND STEP
subtract 3 from the right-hand side as well as on the left-hand side
![4-3](https://tex.z-dn.net/?f=4-3%20%3C-2x%2B3-3%3C9-3)
SOLVING THE REMAINING COMPLETE COMPRESSION
![1 < -2x < 6](https://tex.z-dn.net/?f=1%20%3C%20-2x%20%3C%206)
Divide all parts by -2
- Please note that multiply or divide an inequality by a negative number flips the inequality sign.
so the expression becomes
![\frac{1}{-2}\:](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B-2%7D%5C%3A%3C%5C%3A%5Cfrac%7B-2x%7D%7B-2%7D%5C%3A%3C%5C%3A%5Cfrac%7B6%7D%7B-2%7D)
![\frac{1}{-2}\:>x\:](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B-2%7D%5C%3A%3Ex%5C%3A%3C%5C%3A-3)
Hence, from the explanation, we conclude that in the second step, 3 should have been subtracted from the right side as well on the left side.
I think red I'm not sure maybe not I'm sorry.